Analisis Koefisien Rezim Aliran (Kra) Berdasarkan Permenhut No: P.61/2014 (Studi Kasus: Sub Das Batang Sinamar, Sub Das Batang Ombilin Dan Sub Das Lubuk Ambacang) - Sutopo Sutopo; Yohanna Lilis H; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Activities to determine the development of satisfaction, quality, and continuity of water flow from watersheds / sub-watersheds, namely by monitoring and evaluating water systems, one of the monitoringand evaluation of water systems using KRS (River Regime Coefficient) Based on Permenhut No: P.61 / 2014 conducted in Sub Batang Sinamar watershed, Batang Ombilin watershed and Lubuk Ambacangwatershed. This watershed was chosen because in this area floods occur every year. The data used are Indragiri Hulu watershed map data and discharge data to analyze the KRA value. The results of KRAanalysis in the Batang Sinamar Sub-watershed from 2010 to 2018 amounted to 35.40 included in the classification of